A comprehensive review of hybrid supercapacitor from transition metal and industrial crop based activated carbon for energy storage applications. (March 2023) - Mandal, Sujata; Hu, Jiyao; Shi, Sheldon Q.
Abstract: The steady demand for sustainable and clean energy, and depletion of fossil fuel has accelerated the research on electrochemical energy storage. Supercapacitors (SCs) are effective electrochemical energy storage devices which find extensive applications, and the performance of these devices is determined by the composition and configuration of the electrodes. Carbon-based materials and transition metal oxides are considered efficient super-capacitive materials. Bio-based activated carbon, owing to its nontoxicity, easy availability, and biodegradability can be a suitable precursor material for the applications of SCs. In this work, an overview of the recent progress and applications of hybrid supercapacitors that utilize activated carbon derived from industrial energy crops, like jute, kenaf, hemp, bamboo, etc. along with transitional metal oxides, as electrode materials is presented. This article also summarizes the performance of SCs in terms of energy and power density, market growth, and future research direction. The utilization of non-feed crop-based supercapacitors hopefully will contribute to a greener and brighter future. Graphical Abstract: ga1